2017
DOI: 10.1186/s12913-017-2766-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation modeling for stratified breast cancer screening – a systematic review of cost and quality of life assumptions

Abstract: BackgroundThe economic evaluation of stratified breast cancer screening gains momentum, but produces also very diverse results. Systematic reviews so far focused on modeling techniques and epidemiologic assumptions. However, cost and utility parameters received only little attention. This systematic review assesses simulation models for stratified breast cancer screening based on their cost and utility parameters in each phase of breast cancer screening and care.MethodsA literature review was conducted to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…37,[39][40][41] Six reviews, mainly based on the same original evidence, reported resource use or costs of breast cancer follow-up (Appendix 5). 22,30,35,[42][43][44] The highest rate of resource use was for follow-up visits and follow-up mammography, 44 while the frequency of visits decreased twice in the initial 4 years after F I G U R E 2 The conceptual framework of the review treatment. 43 The follow-up costs could be affected by poor continuity of the doctor-patient relationship, with patients seeing multiple doctors during the follow-up and doing almost twice the recommended number of visits.…”
Section: The Determinants Of Breast Cancer Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,[39][40][41] Six reviews, mainly based on the same original evidence, reported resource use or costs of breast cancer follow-up (Appendix 5). 22,30,35,[42][43][44] The highest rate of resource use was for follow-up visits and follow-up mammography, 44 while the frequency of visits decreased twice in the initial 4 years after F I G U R E 2 The conceptual framework of the review treatment. 43 The follow-up costs could be affected by poor continuity of the doctor-patient relationship, with patients seeing multiple doctors during the follow-up and doing almost twice the recommended number of visits.…”
Section: The Determinants Of Breast Cancer Costsmentioning
confidence: 99%
“…47 Another review estimated the costs of personalizing screening intervals considering an individual's cancer risk, concluding higher cost (2000-2500 USD, 2014) for a higher risk population. 42 While mammography was a target intervention in most of the reviews, three publications reported BCS costs for the other screening approaches ( Table 1). Zelle et al (2013) reported that CBE can be a cost-effective screening method for some low-income settings (India, Ghana, and Egypt).…”
Section: Determinants Of Breast Cancer Screening Costs and Cost-effmentioning
confidence: 99%
“…Cost and utility effects of risk‐stratification are largely ignored. A full systematic review of simulation models for stratified BC screening conducted by Arnold 23 suggests that risk‐stratification has no considerable cost implication but being declared high‐risk could significantly reduce QoL. We identified two studies 32,33 where results suggest that an increase in the cost of risk stratification might cause the risk‐based strategy not to be cost‐effective compared to ABS (WTP threshold £30 000/QALY gained).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, two systematic reviews have been published. Arnold 23 conducted a literature review focussing on the analysis of modelling techniques. Roman et al 24 reviewed previous studies on the effectiveness of RBS and the risk of bias.…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews (19,132) have previously explored the outcomes of economic evaluations relating to breast screening programmes. Schiller-Fruhwirth et al (19) reported on the lack of breast screening specific utilities and insufficient reporting of validation in their review of economic models.…”
Section: Principal Findingsmentioning
confidence: 99%